The Influence of Green Marketing and Brand Image on Interest in Buying Aqua Packaged Drinking Water - Kewo, Stela Theodora; Ady, Sri Utami (Journal of Innovation in Management, Accounting and Business, 2024)
Nowadays, consumers are increasingly concerned about environmental issues, so businesses that do not meet these expectations will experience difficulties in business competition. Green marketing is a concept that fulfills consumers' desires to care more about the environment. Likewise, brand image is a consumer perspective such as design, brand and logo that can influence consumer decisions in selecting products. This research aims to examine the influence of green marketing and brand image on interest in buying bottled drinking water. The research population is all agents selling bottled aqua drinks in Minahasa Regency. 92 samples were taken which were then tested using multiple linear regression analysis with an alpha of 5% using SPSS 23 software. Data was collected by providing a questionnaire filled in by the customer. The research results show that green marketing partially has a positive and significant influence on interest in buying. Likewise, brand image has a positive and significant influence on interest in buying. Simultaneously, green marketing and brand image have a positive and significant influence on interest in buying aqua bottled drinking water.